PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PT. CIPTA PRIMA KONTRINDO PALEMBANG - SUMATERA SELATAN - Yuniarti Anwar (Jurnal Ilmiah Ekonomi Global Masa Kini)
Effect of Compensation and Motivation on Employee Performance of PT.Cipta Prima Kontrindo Palembang Sumatera Selatan. The formulation of the problem in this research is "Is there any influence of compensation and motivation to the work performance of PT. Cipta Prima Kontrindo Palembang Sumatera Selatan? "The purpose of this study is To determine the effect of compensation and motivation on employee performance PT. Cipta Prima Kontrindo Palembang Sumatera Selatan. The location of this research was conducted at PT. Cipta Prima Kontrindo Jl. Lunjuk Jaya No. 100 Rt. 049 Rw. 014 Exod. Lorok Pakjo Kec. Ilir Barat I Palembang. Jenis Research is associative with the data used is primary data. Data collection technique used is Questionnaire. The analytical method used is qualitative and quantitative method using multiple linear regression. Based on result of research with multiple liner regression done on variable of Compensation (X₁) and Motivation (X₂) to Work Achievement (Y) with equation Ŷ = 0,125+ 0,345X1 + 0,586X2. Conclusion 1) Simultaneously there is a significant influence between Compensation and Motivation on Employee Performance. 2). Partially indicates that there is a significant influence Compensation on Employee Performance PT. Cipta Prima Kontrindo Palembang. Advice, the proportional leadership should pay attention to the compensation and incentives fair and reasonable to employees. So that employees are motivated to work and give performance to the company PT.Cipta Prima Konrindo Palembang.Keywords : Compensation, Motivation, and Job Performance